Disruptive innovation at the base-of-the-pyramid: Negotiating the missing links - Esnah Dzimba; John Andrew van der Poll (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The disruptive innovation framework has become a topical issue in recent years. Despite its popularity, as well as the perceived strategic advantages it bestows on entrant firms, little is known about the disruptive innovation capability of new-technology-based firms (NTBFs) in the South African context. This article explores the contextual factors that influence disruptive innovation capability in South Africa's base-of-the-pyramid (BoP) environment and how, given the specifics of this operating environment, entrepreneurs strategize for disruptive innovation capability. Following the development of a conceptual framework, we used a grounded theory approach to conduct in-depth interviews with purposefully selected stakeholders in the NTBF incubation sector. Our findings show that South Africa has the catalytic socio-economic dynamics to encourage the development of disruptive innovations. However, despite having fairly robust institutions in the entrepreneurial ecosystem, these fall short of enabling the innovation capability of NTBFs, owing to the poor-quality linkages between and among institutions within the ecosystem. On the strength of these findings, we synthesised a framework of disruptive innovation capability in BoP environments that highlights the contextual factors that influence disruptive innovation capability. Specifically, we demonstrate how the quality of linkages in the entrepreneurial ecosystem influences the innovation outcomes for innovators.
Keywords: 650; base-of-the-pyramid (BoP); disruptive innovations; emerging economies; grounded theory; national systems of innovation (NSI); new technology-based firm (NTBF); resource-constrained innovations